2021
DOI: 10.3389/fpsyt.2021.721690
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Influences on Theory of Mind Impairment in Opioid Dependent Patients

Abstract: Theory of mind (ToM) is an aspect of social cognition impaired in different addictive disorders, including opioid addiction. This study aimed at replicating ToM deficits in opioid dependent patients undergoing opioid maintenance treatment (OMT) and exploring the influence of substance use related variables, executive functions and childhood maltreatment on ToM in opioid dependent patients. 66 opioid dependent patients were tested using the Movie for Assessment of Social Cognition (MASC) and compared with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Data collection and diagnostic procedures also were performed by trained medical staff and a senior psychiatrist. A study description of sample 2 has previously been published ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection and diagnostic procedures also were performed by trained medical staff and a senior psychiatrist. A study description of sample 2 has previously been published ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…In animals, μopioid agonists also influence the social approach and withdrawal behavior depending on the dose, duration of dosing, and the social context [8]. Clinical studies in humans have shown that opiate addicts under low-dose opiate maintenance treatment display deficits of social interaction and social cognition with autism-like behaviors [8,[26][27][28]. Moreover, opioid antagonists may improve hyperactivity and restlessness symptoms in autism [4,29].…”
Section: Introductionmentioning
confidence: 99%